POWER OF CHOICES IN LANGUAGE LEARNING - Mary Chang (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Preparing students to score well on standardized English language tests like the TOEFL or TOEIC requires more than knowing the parts of the test and the test-taking techniques in a timed assessment. Many Japanese students ask for word or vocabulary lists they can study to tackle the listening and reading sections of the test. A more useful skill is identifying parts of words (affixes and base forms), their meaning, and what forms they take when used in a different part of speech (noun, verb, adjective, or adverb forms). Students find words from other English sources such as textbooks, novels, magazines, movies, or conversations. They are given listening and reading websites that have passages leveled for word and sentence complexity and asked to do the exercises connected with those audio files/ reading passages. How does level choice influence the sense of progress and language learning? Three Japanese university classes are asked to select the level of listening and reading tasks (from beginning to upper-intermediate) for their weekly vocabulary review journal. A survey after each week’s assignments asks the reasons for choosing a particular level and the student’s perceived ease/ difficulty with the exercises plus their perceived skill advancement. The presentation will review the results of these surveys as well as the extent of having a choice plays a role in language learning.